The effects of mindfulness stress reduction program on postmenopausal women's menopausal complaints and their life quality - Sener, Nurdilan; Tashan, Sermin Timur (Elsevier Sci Ltd, 2021)
Aim: This study was carried out to define the effect of the Mindfulness Stress Reduction Program (MBSR) applied among postmenopausal women on their menopausal complaints and quality of life. Material and method: The study was conducted with a quasi-experimental design. The sample consisted of 118 women, including 55 in the experimental group and 63 in the control group. A Personal Information Form, the Mindful Attention Awareness Scale (MAAS), the Menopausal Symptoms Rating Scale (MRS) and the Menopause Specific Quality of Life Questionnaire (MENQOL) were used to obtain the participants' data. An 8-week Mindfulness Stress Reduction Program was applied among the women in the experimental group. After the pretest, both groups completed the midtest at eight weeks and the posttests covering MAAS, MRS and MENQOL at 16 weeks. The data were analyzed by using descriptive statistics, independent-samples t-test, chi-squared test, ANOVA and Cronbach's alpha analysis. Findings: It was observed that, in the midtest and posttest, there was a significant difference between the MRS total and psychological complaints domain scores of the women in the experimental and control groups (p < 0.05). In the midtest, there was a significant difference in the vasomotor, psychosocial, sexual domains and scale total scores between the experimental and control groups (p < 0.05). In the posttest of the women in the experimental and control groups, a significant difference was found between these groups in the MENQOL vasomotor area, psychosocial area, physical area domains and scale total scores (p < 0.05). Result: The MBSR program reduced the menopausal symptoms and increased the quality of life of the postmenopausal women.
Keywords: Postmenopause; Mindfulness stress reduction program; Menopausal symptoms rating scale; Menopause specific quality of life questionnaire